Analisis Framing Pemberitaan Konser Blackpink di Stadion Gelora Bung Karno dalam Media Liputan6.com dan Kompas.com ) - Ade Irma; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how a media creates framing of the news it writes. The method used in this research is a qualitative-descriptive method. The subjects in this study were two online news media, namely Kompas.com and Liputan6.com with the object of research being one text of each news. "Menpora Ensures BLACKPINK BORN PINK Concert Can't Use GBK Main Stadium" and "Explanation of Menpora Bans Concerts at GBK, But Allows Jokowi Volunteer Events." The results of the framing analysis of the two media found several differences, especially in the syntactical elements. On the media Kompas.com the title in the news does not seem offensive. Meanwhile, in the Liputan6.com media, the headline slightly alluded to the Bung Karno Stadium's decision not to be used by other activities.